Pelaksanaan Model Pembelajaran Sains Berbasis Multisensori-Ekologi di Taman Kanak-Kanak Aisyiyah 6 Kota Padang - Yaswinda Yaswinda; Syahrul Ismet (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2017)
This study aims to describe the implementation model on science-based on multisensory-ecology in group A of Aisyiyah 6 Padang City. The study was conducted from August until November (2017). The method was used in this research is a qualitative approach. Data were collected through observation, interviews, and literature studies. Data were analyzed descriptively. The Results of the study are the implementation model on science-based on multisensory-ecology. The study concluded that the instructional model on science-based on multisensory-ecology can upgrade cognitive abilities, social-emotional and physical of children in group A of kindergarten Aisyiyah 6 Padang. Implications of the research are the creation of an instructional model renewal of science for early childhood. Recommendations research is the model on science-based on multisensory-ecology should be studied seriously by teachers before applying this model.